A new mitochondria-targeted ratiometric fluorescent probe based on diketopyrrolopyrrole for imaging endogenous HOCl in living cells. Issue 23 (16th October 2018) - Xie, Xiaoxu; Wang, Jian; Yan, Yongchao; Zhang, Xiao; Liu, Chenchen; Yang, Ji; Hua, Jianli
Abstract : Ratiometric fluorescent probe (PTZ-TDPP ) for HOCl detecting based on diketopyrrolopyrrole (DPP) and phenothiazine platform was designed and synthesized.PTZ-TDPP could target mitochondria and successfully applied in detecting endogenous HOCl in living RAW 264.7 cells. Abstract : Hypochlorous acid (HOCl) is a highly effective oxidant produced during phagocytosis and plays an important role in a variety of physiological and pathological processes. In this work, a new ratiometric fluorescent probe (PTZ-TDPP ) based on a diketopyrrolopyrrole (DPP) and phenothiazine platform, was firstly designed and synthesized for the selective detection of HOCl.PTZ-TDPP showed an obvious color change from purple to pink along with a distinct fluorescence change from bright red to yellow in response to HOCl. The limit of detection towards HOCl was calculated to be 190 nM. For biological applications, PTZ-TDPP is of great development potential in detecting endogenous HOCl in living RAW 264.7 cells. A co-localization study employing MitoTracker Green showed thatPTZ-TDPP was specifically located in the mitochondria of RAW 264.7 cells. Therefore, PTZ-TDPP has great potential for the detection of endogenous HOCl in living cells.